Overview of Hepatitis B and Human Immunodeficiency Virus Coinfection - Gamde, Solomon M; Yakon, Shammah Joy; Daniel, Abigail Abi; Alexandra, Philip; Bukola, Ajide A (International Journal of Human and Health Sciences (IJHHS), 2025)
Hepatitis B Virus (HBV) and Human Immunodeficiency Virus (HIV) co-infection is a major public health issue, especially in areas where both viruses are common. Despite the serious health problems associated with having both HBV and HIV, the specific immune interactions between these viruses are not fully understood. This review looks at how these two viruses interact in the body, affecting the immune system and overall health. When someone has both infections, it can lead to faster damage to the immune system, higher levels of virus in the body, and more severe liver problems, including cirrhosis and liver cancer. This research should aim to identify specific immune responses, which could lead to better treatment options for people with both infections. Improved understanding may also help with vaccine development and optimize the use of current antiviral treatments. Treatments like antiretroviral therapy, which can help manage both HBV and HIV, have shown effectiveness. However, treating both infections at the same time is complicated due to issues like drug resistance, a condition known as immune reconstitution inflammatory syndrome (IRIS), and overlapping side effects from the medications. This review also points out important gaps in research, especially regarding the long-term effects of having both infections and how to improve treatment plans for better patient outcomes. Future research should focus on new treatment methods, the role of immune boosters, and personalized treatment strategies to tackle the unique challenges of HBV-HIV co-infection. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 200-206